New trends, more concentration? The patterns of enrollment distribution in Brazilian higher education between 2010 and 2019 - Coelho, Ruan de Oliveira; Penha, Pedro Henrique Elgaly da; Milanski, Bruna Aparecida (Plural, 2022)
In recent decades, there has been a global expansion of vacancies in higher education systems in several countries, which has been accompanied by a process of growing commodification in this segment of education. That is, the private sector has increasingly taken on more participation in its offer, and this has resulted, among other things, in an intensification of the phenomenon of institutional diversification. Foreign research on the subject focuses precisely on this diversification, but this article aims to analyze the Brazilian case also from the perspective of the concentration of enrollments in the last decade, which was the one with the greatest growth of emerging models of educational offer, such as the distance modality. The results point to the occurrence of a heterogeneous variation in the concentration of enrollments, in various types of courses, but for a homogeneous distribution in the two years analyzed, with a more accentuated concentration in the final year.